Mechanical Property Degradation of Transmission Wire Rope Caused by Different Wear Evolution - Xiangdong Chang; Fahui Shi; Xiao Chen; Yuxing Peng; Yu Tang; Wenjie Xiao; Ran Hu (Lubricants)
Steel wire rope serves as a critical load-bearing and transmission component in the transportation equipment utilized in coal mines. It exhibits various forms of damage during prolonged service, which significantly jeopardizes the safety reliability of the transportation equipment. To investigate the formation process of the surface wear of steel wire rope and its influence on mechanical properties, the tribological evolution and performance degradation of the transmission wire rope under rope–sheave contact and rope–rope contact were studied in this paper. The wire rope’s friction coefficient (COF) is stable between 0.7 and 0.8 under two contact conditions. It is more likely to lead to the accumulation of frictional heat under the condition of rope–sheave contact. The primary wear mechanisms of transmission wire ropes are adhesive wear and fatigue wear. Additionally, the wear evolution leads to the nonlinear degradation of the tensile strength and bending fatigue life of the wire rope, and the wear damage caused by rope–sheave contact is more harmful. As the sliding distance between the wire rope and the sheave increases, the breaking force decreases from approximately 48 kN to 23 kN, and the number of bending fatigues of the wire rope before scrapping is reduced from approximately 6200 times to 200 times.